The social organization of errors and the manifestation of rework: learning from narratives of practice - Love, Peter; Matthews, Jane (TAYLOR & FRANCIS LTD, 2022)
Despite the considerable amount of research that has examined rework causation in construction, it remains an inherent problem that can potentially result in adverse project outcomes. This situation has arisen as studies have tended to ignore the social organization of errors (i.e. the pattern of relationships and social interactions between and among individuals and teams). Instead, studies have adopted a ‘reductionist view’ of rework causation by identifying its proximal and root causes rather than addressing the conditions resulting in its manifestation. This paper uses a case study approach with a sense-making lens to create a series of narratives of rework events that arose while constructing a transport mega-project. By making sense of the context surrounding the error events, it is revealed rework manifests from failures in ‘negotiated order’ which stems from role ambiguity, misunderstandings, misinterpretations, and break-downs in communications and interactions between people and organizations. As a consequence of these findings, their theoretical and practical implications arising from the research are discussed.